Addressing the worldwide hepatocellular carcinoma: epidemiology, prevention and management - Hrishikesh Samant; Hosein Shokouh Amiri; Gazi B. Zibari (2021)
Hepatocellular carcinoma (HCC) is the sixth most common cancer in the world with rising incidence. Globally, there has been substantial variation in prevalence of risk factors for HCC over years, like control of viral hepatitis in developing countries but growing epidemic of fatty liver disease in developed world. Changing epidemiology of HCC is related to trends in these risk factors. HCC remains asymptomatic until it is very advanced which makes early detection by surveillance important in reducing HCC related mortality. Management of HCC. depends on stage of the tumor and severity of underlying liver disease. At present, resection and transplant are still the best curative options for small HCC, but recent advances in locoregional therapy and molecular targeted systemic therapy has changed the management for HCC at intermediate and advanced stages. This review is overview of global epidemiology, prevention, surveillance and emerging therapies for hepatocellular carcinoma.